Differential susceptibility to allostatic load and educational inequalities in coronary heart disease. (30th September 2020) - Hicks, B; Veronesi, G; Ferrario, M; Cesana, G; Iacoviello, L; Palmieri, L; Kuulasmaa, K; Soderberg, S; Sans, S; Kee, F
Abstract: Background: Differential exposure to lifestyle factors may mediate the association between education and cardiovascular disease (CVD). However, differential susceptibility (the effect of exposure to the same "dose" of risk factors differs across groups) may also elevate CVD risk but the causal pathways remain unclear. Allostatic Load (AL) is a marker of cumulative biological burden resulting from mal-adaptation to chronic stressors. We aimed to examine the role of differential exposure and susceptibility to AL and other factors in coronary heart disease (CHD) educational gradients in Europe. Methods: 51, 328 35-74-year-old participants originally free of CVD from 21 European cohorts in the BiomarCaRE consortium were identified and followed for a median of 10 years to their first CHD event. We defined an AL score as the sum of z-scores of 8 markers from the cardiovascular, metabolic, and inflammatory systems. To investigate the mediating role of AL (and smoking, alcohol and BMI) on educational differences in CHD incidence we applied marginal structural models and three-way decomposition on gender-specific additive hazards models. Results: AL was a significant mediator of the association between educational status and CHD. The highest proportion mediated was observed in women, with 28% (95%CI 20% to 44%) attributable to differential exposure and 8% (95%CI 0% to 16%) to differential susceptibility. In men, AL mediated 16% of the increased CHD risk in the less educated, with 2% (95%CI 0%-6%) attributable to differential susceptibility. The effects of smoking, alcohol and BMI were relatively small for men and women, with a limited role of differential susceptibility. Conclusions: While we found evidence of differential susceptibility to AL on CHD, effects were modest and the mediating effect of AL (and other lifestyle factors) was predominately via differential exposure. Controlling disproportionate exposure to AL may help reduce CHD morbidity among those with lower education. Key messages: Educational inequalities in coronary heart disease in Europe were predominantly driven by differential exposure rather than susceptibility to allostatic load and other lifestyle factors. Controlling disproportionate exposure to AL may help reduce coronary heart disease morbidity among those with lower education.